2022
DOI: 10.4308/hjb.30.1.140-147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Mannan-Oligosaccharide (Mos) and Multi-Species of Bacillus on Growth and Feed Utilization in Leopard Coral Grouper Plectropomus leopardus Juvenile

Abstract: This study assessed the growth and feed utilization in leopard coral grouper Plectropomus leopardus juvenile fed dietary prebiotic mannan-oligosaccharide (MOS) and multi-species of probiotic bacteria (Bacillus cereus BS6, B. subtilis BS3, and B. amiloliquefaciens BS4). The experiment was performed by feeding four replicates groups of juveniles weighing 3.61±0.60 g on four experimental diets, and each diet included: only MOS (PRE); the multi-species of Bacillus (PRO); a combination of MOS and the multi-species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…These findings align with previous studies conducted on rainbow trout (Oncorhynchus mykiss (Walbaum)) fed with MOS 0.2% (Mínguez et al 2016), milkfish (Chanos chanos (Fabricius)) fed with MOS 0.3% (Harikrishnan et al 2023), and Atlantic salmon (Salmo salar L.) fed with MOS concentrations of 0.5% and 1.0% (Kazlauskaite et al 2022). MOS has been documented to improve functional gut health by increasing digestive enzyme activity to boost nutrient digestibility and the absorption of lipids, proteins, and phosphorus for better growth performance with a lower FCR (Flores-Kossack et al 2020, El-Saadony et al 2021, Xue et al 2022, Sudewi et al 2023. Electron microscopy and transmission electron microscopy showed that gilthead seabream (Sparus aurata L.) supplemented with MOS 0.2% had a greater capacity for nutrient capture Gary Petol Felix et al 39 thanks to an increase in microvilli density and length in both the anterior and posterior gut regions (Dimitroglou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings align with previous studies conducted on rainbow trout (Oncorhynchus mykiss (Walbaum)) fed with MOS 0.2% (Mínguez et al 2016), milkfish (Chanos chanos (Fabricius)) fed with MOS 0.3% (Harikrishnan et al 2023), and Atlantic salmon (Salmo salar L.) fed with MOS concentrations of 0.5% and 1.0% (Kazlauskaite et al 2022). MOS has been documented to improve functional gut health by increasing digestive enzyme activity to boost nutrient digestibility and the absorption of lipids, proteins, and phosphorus for better growth performance with a lower FCR (Flores-Kossack et al 2020, El-Saadony et al 2021, Xue et al 2022, Sudewi et al 2023. Electron microscopy and transmission electron microscopy showed that gilthead seabream (Sparus aurata L.) supplemented with MOS 0.2% had a greater capacity for nutrient capture Gary Petol Felix et al 39 thanks to an increase in microvilli density and length in both the anterior and posterior gut regions (Dimitroglou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among all the treatments, significant growth improvement with the highest nutrient utilization was noted in the juvenile Asian seabass fed SSF 0.025% + MOS 0.05%, which can likely be attributed to multiple beneficial functions of each of the feed additives. The literature indicates that MOS acts as a prebiotic that stimulates the growth and colonization activity of beneficial bacteria in fish guts (El-Saadony et al 2021Flores-Kossack et al 2020, Sudewi et al 2023, Xue et al 2022, whereas Aspergillus niger, through solid-state fermentation (SSF), produces a range of enzymes that break down complex carbohydrates, proteins, and fibers of aquafeed into simpler, more digestible forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation